Designing a Marketing Information System for Pesona Permata Hijau 2 Housing Using the Waterfall Method (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2023)
Housing is an area or region that consists of several residential units or buildings with clear construction regulations and a uniform and synchronized form/pattern without any differentiation. At this time, there are still many housing property companies that promote their properties manually. One of the property companies that still promotes their marketing manually is The Housing Pesona Permata Hijau 2. Pesona Permata Hijau Housing 2 is one of the housing estates located near Jalan Raya Cibogo, Subang Regency In the process of marketing Housing Pesona Permata Hijau 2 is still done manually, namely by distributing brochures, placing banners, and promoting at major events. Technological advances are currently widely used by various industries, one of which is used as a property marketing medium such as housing. As a use of information technology that exists at this time, the right solution to overcome the above problems is to build a Housing Marketing Information System Pesona Permata Hijau 2 using the Waterfall method. The stages of the Waterfall method carried out in the development of this software consist of analysis, design, coding, and testing. With this system, it is hoped that it can facilitate the marketing process of the marketing division, and prospective buyers can easily get detailed information about the housing.